ONLINE CUSTOMER REVIEWS AND ONLINE CUSTOMER RATINGS ON PURCHASE DECISIONS - Ependi, Ependi (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The purpose of this research is to identify the number of e-commerce enthusiasts in choosing the need for online shopping to be large, for young people, who like to shop online quickly outperform their competitors. and to recognize what attracts the attention of consumers so they decide to buy products through Shopee. Using a quantitative descriptive approach, collecting questionnaires or data form distributed through a questionnaire google forms total of 100 respondents. The results show that online customer reviews and also online customer ratings have an influence on the purchase decision is positive and significant. The coefficient of determination test shows that the independent variable of the study can explain 80.4% of the purchase decision, and 19.6% can be explained by several factors outside the model studied.